Neuropilin 2 in osteoblasts regulates trabecular bone mass in male mice - Verlinden, Lieve; Doms, Stefanie; Janssens, Iris; Meyer, Mark B.; Pike, J. Wesley; Carmeliet, Geert; Verstuyf, Annemieke (Frontiers in Endocrinology, 2023)
Neuropilin 2 (NRP2) mediates the effects of class 3 semaphorins and vascular endothelial growth factor and is implicated in axonal guidance and angiogenesis. We demonstrated NRP2 expression in osteoblasts and osteoclasts and showed that male and female global Nrp2 knockout mice have a reduced bone mass accompanied by reduced osteoblast and increased osteoclast counts. We now show that Nrp2 expression is induced by 1,25-dihydroxyvitamin D3 in osteoblasts and is associated with enrichment of the vitamin D receptor in an intronic region of the Nrp2 gene. In male mice, conditional deletion of Nrp2 in osteoblast precursors and mature osteoblasts recapitulated the bone phenotype of global Nrp2 knockout mice, with a reduced cortical cross-sectional tissue area and lower trabecular bone content. However, female mice with reduced osteoblastic Nrp2 expression display a reduced cross-sectional tissue area but have a normal trabecular bone mass. Treatment with the bone anabolic vitamin D3 analog, WY 1048 (0.4 µg/kg/d, 14 days, ip), resulted in a similar increase in bone mass in both genotypes and genders. Deleting Nrp2 from the osteoclast lineage did not result in a bone phenotype, even though in vitro osteoclastogenesis of hematopoietic cells derived from mutant mice was significantly increased. Moreover, treatment with a high dose of 1,25-dihydroxyvitamin D3 (0.5 µg/kg/d, 6 days, ip), to induce osteoclast-mediated bone resorption, resulted in a similar reduction in trabecular and cortical bone mass. In conclusion, osteoblastic Nrp2 expression is suggested to regulate bone homeostasis in a sex-specific manner.